PSYCHOSOMATICS OF TEENAGERS AND YOUNG PEOPLE AS A RESULT OF SUPPRESSED FORBIDDEN EMOTIONS IN FAMILY EDUCATION (Psychology Travelogs, 2023)
The article analyzes the latest theoretical studies on psychosomatics, which revealed that some diseases arise under the influence of psychogenic stress factors that caused the experience and suppression of emotions. The types of categories of forbidden, restrained, repressed experiences and how they manifest themselves in life are presented. The risk factors that are more likely to lead to psychosomatic illness in childhood and adolescence are described. Practical diagnostic experience of psychosomatic complaints of teenagers and young people is collected, where specific symptoms and correlation between emotions that are not released as allowed and were suppressed, displaced during family upbringing, and psychosomatic symptoms due to the restraint of stressful emotions by a young person, on the other hand, are investigated. Understanding these connections can provide an opportunity to timely and effectively address the disorder, including through psychocorrection and psychotherapy in individuals of this sensitive age period, which is emotionally intense, full of experiences, shyness, reduced critical thinking, unmet needs, and wishes. If a child has his or her own needs that differ from the interests of the parents, there is a risk that at a young age these forbidden emotions will be suppressed and blocked, and the young person will say: I do not understand what I really want and who I really am, which makes further self-determination difficult and means denying and displacing some part of himself or herself, his or her personality. But this part of the personality exists and begins to influence uncontrollably, causing diseases, problems, and unhealthy relationships. The article describes what specific educational conditions affect the restraint of emotions and what stress factors make an adolescent experience such negative emotions as fear, sadness, longing, sadness, etc., and it is these emotions that are the link between the psychological and somatic spheres of life. The relevance of the study emphasizes the importance of learning to recognize, realize and adequately express all feelings for mental and physical health in the future.
Keywords: psychosomatics of teenagers and young people; stress; worries; forbidden repressed emotions; family education